Relationship between starting and finishing position in World Cup BMX racing - Rylands, L.; Roberts, S. J. (International Journal of Performance Analysis in Sport, 2014)
The BMX start is one of the most important aspects of BMX racing and has been deemed by coaches as one of the strongest determining factors of finish line placing. The present study analysed the correlation between elite BMX riders and their relative position at the start of a BMX race in relation to finish line placing. Data from 348 riders results in 175 elite races in the four 2012 Union Cycliste Internationale (UCI) world cup events were analysed. Time gates were placed in four positions around each BMX track and the data sets were analysed using Kendall`s tau-b bivariante correlation. A strong correlation was established at the second time gate for both males (t=0.581, P<0.01) and females (t=0.571, P<0.01). The correlation between riders` final placing was greater in positions 1st to 3rd (t=0.586, P <0.01. 4th to 8th t=0.249, P <0.01) compared to riders placed 4th to 8th (t=0.519, P <0.01. 4th to 8th t=0.372, P <0.01.) for both male and female riders respectively. In conclusion, a strong correlation exists between riders position 8-10 s into a race. Therefore, focusing on a riders` ability to gain placings at the start of a race will have an effect on their finish line position.